FACTORS CAUSING THE DUPLICATION OF THE NUMBER OF MEDICAL RECORD DOCUMENTS IN BROMO PUBLIC HEALTH CENTER - valentina valentina (STIKes Hang Tuah Pekanbaru, 2020)
Public Health Center is a first-level health facility that requires good management of medical records in order to achieve orderly administration. The purpose of this study is how the factors that cause the duplication of medical record numbers in Bromo Health Center Medan. This type of research is descriptive research. The population is the entire medical record of outpatients in Bromo Health Center as many as 4262 medical records. While the sample was 366 medical record files and the number of officers was 6 people. The sampling technique uses accidental sampling. Data collection was carried out using the observation method using an observation sheet and the interview method with a questionnaire. Data were analyzed descriptively to see the cause of the duplication of medical record document numbering based on patient factors, staff factors and medical record management system factors. The results showed that the number of duplicate medical record documents at the Bromo Health Center in Medan was 8.74%. Factors causing duplication are patients not carrying medical identity cards, medical records officer qualifications that are not appropriate, no tracers, expedition books and Standard Operating Procedures (SPO) in the storage section, numbering system and the use of non-standard family folders. It is expected that the Public Health Center will search and rearrange lost and scattered medical record documents, recruit medical record officers according to the competencies and qualifications of the formal medical record education, and provide medical record training as needed, create Standard Operating Procedures (SPO), change numbering and alignment of medical records, using tracers and expedition books and outreach to patients about the use of a Medical Identity Card .